A Systematic Review of Teachers' Obstacles in Implementing Differentiated Learning in Junior High Schools - Safriana, Safriana; Irfan, Ade; Iramadhani, dwi; Ula, Mutammimul (Universitas Syiah Kuala, 2024)
Education plays an important role in developing human potential to face future challenges. One of the newest concepts in education is differentiated learning, which aims to meet the individual needs of students with tailored teaching strategies. This study uses the Systematic Literature Review (SLR) method with the PRISMA approach to explore the obstacles faced by teachers in implementing differentiated learning in junior high schools. A literature search was conducted through Google Scholar with related keywords between 2020-2024, resulting in 19 articles that met the inclusion criteria. The results of the analysis show that the main obstacles include teacher readiness, technology limitations, and inadequate time allocation. The proposed solutions include increased teacher training, the provision of adequate technological resources, and better planning for time allocation. Support from schools and supportive policies is also crucial to support the effective implementation of differentiated learning in junior high schools.